LOCAL WISDOM TECHNOLOGY: The Bintang Lhee as Qibla Direction Instrument in Contemporary Aceh - Machzumy, Machzumy; Abdou, Ousmane Salifou; Mursyid, Andi Miftahul Maulidil (UIN Sumatera Utara, 2025)
This qualitative case study explores Bintang Lhee, a traditional Acehnese astronomical method for determining the qibla direction through naked-eye observation of three aligned stars (Alnitak, Alnilam, and Mintaka). The study highlights its technical characteristics and its cultural-religious significance as a form of local wisdom integrating astronomy, faith, and Acehnese identity. Despite its observational limitations, Bintang Lhee represents valuable indigenous knowledge. This study suggests that incorporating such traditional methods into contemporary scholarship can enrich interdisciplinary research in cultural astronomy and indigenous knowledge systems. Keywords: Local Wisdom Technology, Bintang Lhee, Qibla Direction Instrument, Contemporary Aceh